Comparative Study of Diversity of Soil Oribatid Mites (Acari: Oribatida) in Two Different Soil Habitats Near Kolkata, West Bengal, India (Global Journal of Science Frontier Research, 2014)
Soil samples were collected at monthly intervals from two different habitats-a waste disposal site and an agricultural field, near Kolkata, West Bengal. A total of 16 species of oribatid mites of 9 families were recorded from the study sites. The species richness and the abundance of oribatid were maximum in waste disposal site. Whereas, at diversity level, the maximum values for Shannon-Wiener index and Pielou's index of evenness were showed by agricultural field.
Keywords: diversity; oribatid mites agricultural field; waste disposal site